Pre-crisis planning, communication, and management preparing for the inevitable - Olaniran, Bolanle Abodunrin; Williams, David E.; Coombs, W. Timothy (Peter Lang, 2012)
Presents some of the detailed and thorough insights published, and serves as an example of where future research can go. In this book, the editors and contributors offer significant insight into the critical considerations of crisis preparation as well as the importance of anticipation and pre-crisis planning.